Overview of Patient Satisfaction with Information Services and Drug Availability in The Pharmacy Institution of Ibnu Sina Hospital, Makassar - Ismi Azis; Dahliah Dahliah; Nur Fadhillah Khalid; Syamsu Rijal; Iin Widya Ningsi (CV. Inara, 2026)
Pharmacy services are a crucial aspect of healthcare systems, directly influencing patient satisfaction levels. At Ibnu Sina Hospital in Makassar, two key factors affecting patient satisfaction are drug information services and drug availability. Patient satisfaction with these services serves as an indicator of the quality of pharmacy care provided. This study aims to analyze patient satisfaction with drug information services and drug availability at the Pharmacy Department of Ibnu Sina Hospital, Makassar. The study employed a descriptive observational design with a cross-sectional approach. Data were collected using a Likert-scale questionnaire administered to 100 randomly selected respondents. The results showed that patient satisfaction with drug information services ranged from satisfied to very satisfied across all dimensions studied. Empathy received the highest score (84.2%), followed by responsiveness (80.3%) and assurance (82.2%), indicating that patients felt personally cared for and confident in the competence of the pharmacists. Medication availability received a score of 86.5%, indicating that the majority of patients were satisfied with the availability of medications at this hospital. Overall, the results of this study suggest that pharmacy services at Ibnu Sina Hospital, Makassar, have met patient expectations, both in terms of clear and accurate drug information and adequate drug availability. This study recommends that the hospital continue to improve the quality of communication between pharmacists and patients and ensure optimal drug availability to further enhance patient satisfaction.